The Émigré Clergy and the English Church, 1789–1815 - Bellenger, Dominic (The journal of ecclesiastical history, 1983)
The Established Church in the eighteenth century, although not monolithic in its structure, had evolved a delicate counterpoise in its attitude to the fraught question of the relationship between Church and State. The Church was the protector of public religion and morality and as such was protected by the State with a test law and endowment. William Warburton, bishop of Gloucester, was the chief theoretician of the idea of a mutually satisfactory alliance of ‘the two swords’. The ecclesiastical policy of Georgian England, however, owed less to ideology than to the natural development of the English Church after the break with Rome and under the influence of emerging nationalism. The French Church had developed along similar lines to the English – without losing its Roman connections – and there has been a tendency to blur the distinctions between ‘Anglican’ and ‘Gallican’.